Rancang Bangun Sistem Informasi Inventory Barang Dan Aset Berbasis Website Studi Kasus Pemerintah Desa Mojomanis - Sunaryoa, Tria Aprilia Dina; Untari, Erny (Jurnal Sistem Informasi Dan Informatika, 2025)
The Mojomanis Village Government, located in Ngawi Regency, faces challenges in recording goods and asset inventories. The manual system using ledgers and spreadsheets is inefficient, necessitating a computerized solution. This study develops a web-based inventory information system using the waterfall method. The system is built with PHP, HTML (Laravel framework), and MySQL, using Visual Studio Code. Blackbox Testing confirms proper functionality, while the System Usability Scale (SUS) test scores 69.875, placing it in the marginal category on the Acceptability scale and class C on the user acceptance scale. The lower SUS score is attributed to user unfamiliarity with the new system. Despite this, the system aids the Mojomanis Village Government in administrative digitalization.